Infant positioning in daily life may mediate associations between physiotherapy and child development—video-analysis of an early intervention RCT. (June 2016) - Dirks, Tineke; Hielkema, Tjitske; Hamer, Elisa G.; Reinders-Messelink, Heleen A.; Hadders-Algra, Mijna
Highlights: Paediatric physiotherapy may affect parent behaviour during daily activities. COPCA promotes the application of challenging infant positions during bathing. Challenged to sit in bath in early life is associated with better development. Video analysis of daily activities serves insight in parental implementation of intervention. Abstract: Background: Paediatric physiotherapy (PPT) in high-risk infants comprises family involvement, but it is unclear whether parents mediate the intervention effect. We demonstrated in a randomized controlled trial in high-risk infants comparing the family centred programme Coping and Caring for infants with special needs (COPCA) and Traditional Infant Physiotherapy (TIP) that process evaluation revealed associations between COPCA-characteristics and outcome. Aims: To assess whether PPT affects how parents position their infant during bathing and whether this is associated with child outcome. Methods and procedures: 21 infants received COPCA and 25 TIP between 3 and 6 months corrected age. Bathing sessions were videotaped at 3, 6 and 18 months. Time spent with specific infant positions was correlated with quantified PPT-actions and functional mobility at 18 months measured with the Paediatric Evaluation of Disability Inventory (PEDI). Outcomes and results: At 3 and 18 months bathing position was similar in both groups, but differed at 6 months (time spent on sitting: COPCA 77.7%, TIP 39.2%; median difference 32.0% (95% CI: 10.6–50.5%). Sitting-time at 6 months was associated with higher PEDI functional mobility scores. Conclusions and implications: Early PPT may affect parental behaviour, such as infant positioning during bathing, which, in turn, may affect child development.